ANALYSIS OF FUNCTIONAL ELECTRICAL ANNEX DIAGRAMS OF WIND ENERGY CONVERSION SYTEMS - S. G. Polovnikov; V. V. Moroz (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2014)
The paper considers basic concepts in the design of modern wind energy conversion systems (WECS). The analysis of control methods and systems which are capable to realize operational mode  with maximum  output  power  has been presented in the paper.  Functional diagrams of systems for different electric generators, mechanical gears and various combinations of electric power supply and control systems have been have been given in the paper. WECS structures that meet the operational requirements in Belarus have been determined in the paper.